2021
DOI: 10.1093/gbe/evab055
|View full text |Cite
|
Sign up to set email alerts
|

Gene Duplications Trace Mitochondria to the Onset of Eukaryote Complexity

Abstract: The last eukaryote common ancestor (LECA) possessed mitochondria and all key traits that make eukaryotic cells more complex than their prokaryotic ancestors, yet the timing of mitochondrial acquisition and the role of mitochondria in the origin of eukaryote complexity remain debated. Here we report evidence from gene duplications in LECA indicating an early origin of mitochondria. Among 163,545 duplications in 24,571 gene trees spanning 150 sequenced eukaryotic genomes, we identify 713 gene duplication events … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 108 publications
0
30
3
1
Order By: Relevance
“…That is, in a given tree, regardless of how many leaves (mean = 68.8, median = 10, SD = 309.7), at least one gene clade appeared in the tree in which two copies of the gene exist in the same genome and branch as sisters in the tree. This estimate is in contrast to eukaryotes, where 45% of all gene trees uncover recent, within genome duplications by the same criterion ( Nagies et al 2020 ; Tria et al 2021 ). The 6% value for prokaryotes is a first indication of the relative paucity of recent gene duplication in prokaryotic genomes.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…That is, in a given tree, regardless of how many leaves (mean = 68.8, median = 10, SD = 309.7), at least one gene clade appeared in the tree in which two copies of the gene exist in the same genome and branch as sisters in the tree. This estimate is in contrast to eukaryotes, where 45% of all gene trees uncover recent, within genome duplications by the same criterion ( Nagies et al 2020 ; Tria et al 2021 ). The 6% value for prokaryotes is a first indication of the relative paucity of recent gene duplication in prokaryotic genomes.…”
Section: Resultsmentioning
confidence: 71%
“…In prokaryotes, gene duplications are generally thought to be rare ( Lerat et al 2005 ) and whole-genome duplications of the type found in eukaryotes have so far not been reported, even though some prokaryotes can have very high numbers of genomes per cell ( Soppa 2017 ). At the same time, lateral gene transfer (LGT) is very common in prokaryotes ( Ochman et al 2000 ), while the role of LGT in eukaryotic evolution is debated ( Robinson et al 2013 ; Arakawa 2016 ; Nagies et al 2020 ; Tria et al 2021 ). Conversely, the role of gene and genome duplications in eukaryotes is not debated ( Li et al 2003 ; Lynch and Conery 2003 ; Tria et al 2021 ), while the role of gene duplications in the evolution of prokaryotes is hard to quantify because of the confounding effects imposed by LGT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable exception to the described pattern of shared introns between most categories is the low number of shared introns in alphaproteobacterial acquisitions, which were very likely present in the protomitochondrion. It is tempting to speculate that these duplications were due to another mechanism; for example, they may have been the result of serial endosymbiotic gene transfers (15). The protomitochondrion has been widely considered to be the source of introns, even though direct phylogenetic evidence is lacking (12).…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotes are considered more complex than prokaryotes: cells are much larger and contain multiple membrane-bound compartments. Underlying the increase in cellular complexity during the transition to eukaryotes (eukaryogenesis) was an increase in the number of genes caused by gene transfers and gene duplications (14)(15)(16). Mainly genes involved in establishing and regulating a complex cell and relatively few metabolic genes duplicated during eukaryogenesis (16).…”
Section: Introductionmentioning
confidence: 99%